The adaptation of the 'Clinical Outcomes in Routine Evaluation-Outcome Measure' (CORE-OM) from English into a valid Xhosa measure of distress - Campbell, Megan Michelle (Rhodes University, Faculty of Humanities, Department of Psychology, 2013)
In South Africa access to mental healthcare resources is restricted for a number of reasons including language barriers that prevent suitable communication between mental healthcare professionals and African language speaking South Africans. The translation of psychometric tools into African languages has been identified as one method in improving access to psychological services for African language speakers. The Clinical Outcomes in Routine Evaluation - Outcome Measure (CORE-OM) has demonstrated its clinical utility within the United Kingdom (UK) National Healthcare Service (NHS) as a standardised psychotherapy outcome measure that evaluates the degree of psychological distress individuals present with at the start of psychotherapy treatment, and the degree of change that has been effected at the termination of therapy. A measure like the CORE-OM holds valuable clinical utility for the South African context. This thesis argues that the availability of a valid Xhosa version of the CORE-OM would allow for improved access to psychotherapy resources for Xhosa speaking individuals, and allow for the evaluation of the effectiveness of psychotherapy interventions conducted in Xhosa. The CORE-OM developers have provided a translation design and set of guidelines to standardise the translation of the CORE-OM into different languages. However this thesis argues that these guidelines are incomplete. Instead International Test Commission (ITC) guidelines are recommended as a culturally sensitive method to supplement current CORE-OM translation guidelines, in order to generate a valid Xhosa measure of distress. A mixed methods approach is applied which first investigates the construct equivalence and bias of the CORE-OM English version within a South African student population sample, both qualitatively and quantitatively, in order to establish the degree of adaptation required to generate a valid Xhosa version of distress. Next the CORE-OM English version is translated into Xhosa using the five-stage translation design prescribed by the CORE System Trust, supplemented by ITC guidelines. All changes made to the CORE-OM during translation into Xhosa are documented. The CORE-OM Xhosa version is then investigated for reliability and validity. This investigation reveals low internal reliability within the subjective wellbeing domain indicating that these items are less meaningful as depictions of distress within the Xhosa language. A reduced version of the CORE-OM demonstrates strong psychometric properties as a valid Xhosa measure of distress.
Keywords: Psychometrics -- Research -- South Africa; Psychology -- Mathematical models -- Research -- South Africa; Psychological tests -- Research -- South Africa; Mental health services -- Research -- South Africa; Health services accessibility -- Research -- South Africa; Language disorders -- South Africa